Direct means of obtaining CAVI0-a corrected cardio-ankle vascular stiffness index (CAVI)-from conventional CAVI measurements or their underlying variables - Spronck, Bart; Mestanik, Michal; Tonhajzerova, Ingrid; Jurko, Alexander; Jurko, Tomas; Avolio, Alberto P; Butlin, Mark (Physiological measurement, 2017)
Objective: Cardio-ankle vascular index (CAVI) as measured using the VaSera device (CAVIVS, Fukuda Denshi), has been proposed as a stiffness index that does not depend on blood pressure. We have recently shown theoretically that CAVIVS still exhibits blood pressure dependence, and proposed the corrected index CAVI0. The present study aims to establish a method of calculating CAVI0 either (i) from VaSera-reported values of cardiac-brachial and brachial-ankle pulse transit times (tb and tba, respectively) and blood pressure, or (ii) directly from CAVIVS. To derive this method, the relationship among CAVIVS and its scale constants a and b, tb, tba, and blood pressure has to be established. Approach: From data of 497 subjects, eight candidate CAVI parameters were defined and calculated, containing all combinations of left or right tb/tba/blood pressure. Candidates were evaluated through correlation with measured left and right CAVIVS. Correlations were compared statistically. Once the correct candidates were determined, two constants (a and b) required for converting CAVIVS to CAVI0 were estimated through linear regression. Main results: Left and right CAVIVS are calculated using left and right tba; however, both left and right CAVIVS are calculated using right brachial blood pressures and right tb. Constants a and b for conversion of CAVIVS to CAVI0 were estimated to be 0.842 [0.836 0.848] and 0.753 [0.721 0.786] (mean [95%CI]), respectively. Equations to estimate CAVI0 from CAVIVS, and to directly calculate CAVI0 from the VaSera output are provided in this paper, as well as in a directly usable spreadsheet supplement. Significance: Our results permit straightforward calculation of CAVI0 during a study, as well as retrospective estimation of CAVI0 from CAVIVS in already published studies or where the original transit time values are not available, paving the way for thorough comparison of CAVI0 to CAVIVS in clinical and research settings. Novelty and significance Cardio-ankle vascular index (CAVI) as measured using the VaSera device (CAVIVS, Fukuda Denshi), has been proposed as a blood pressure-independent arterial stiffness index. We have recently shown theoretically that CAVIVS still exhibits pressure dependence, and proposed a corrected index, CAVI0. In the present study, we derived equations to directly obtain CAVI0 using data from the VaSera device. Our results permit straightforward calculation of CAVI0 during a study, as well as retrospective estimation of CAVI0 from CAVIVS in already published studies, paving the way for thorough comparison of CAVI0 to CAVIVS in clinical and research settings.